Agility of sustainable product development process framework for Chinese SME products - Zhao, Zhining (2024)
The 4th industrial revolution promoted the development of all countries in the world to get rid of the existing model, and realise the transformation, upgrading of manufacturing, intelligent manufacturing, green manufacturing, and information industry. In a competitive economic environment, SMEs are forced to improve their operational performance and applying efficiency to simplify and speed up the implementation of new product introductions to better control, coordinate, and manage them. However, most of SMEs in China are unable to apply and produce the sustainable products due to lack of knowledge of systematic and appropriate process, especially in the early stage of product development. To fill this gap, a new sustainable design with agility integrated framework is introduced for the sustainability and optimisation development process of China’s SME products. The research focuses on existing methods in product development as well as an agile approach that can be used for better product design. Product designers and SMEs are involved as a respondent through survey by questionnaire. The result acknowledged 24 sustainable product design variables and eight (8) agility management variables that are significant for the sustainability and optimisation product development process. Furthermore, the research also introduced a new framework namely Agility of Sustainable Product Development Process (ASPDP) as a guideline for product developers in the product development process that can effectively be used to produce a sustainable product with possible solutions and resources, systematic and efficient, and quick available in the market as well as can increase product quality, reduce the development cost, and increase profits of the SMEs.